Doživljanje poškodb pri športnikih - Pori, Nika (Šport (Ljubljana), 2023)
An injury is to an athlete an unfortunate event, because of which he must stop with trainings and competitions. In rehabilitation athletes face different physical and psychological challenges. The main goal of this research was to analyse seriousness, the type, and location of the injuries in athletes. Furthermore, we analysed how do they deal with the injury and what is the role of social support and motivation while in recovery. There were 78 professional and amateur athletes gathered in research. Average age of the athletes was 21,7 years (SD= 2,25 years) and they were injured at least once in the last 3 years. The results show that the most of them were injured twice in the last 3 years (43%) and that those were mostly acute, lighter injuries which caused athletes to be absent from their sport about 3-7 days. The most common injury was knee joint injury. After the injury athletes were most likely angry, insecure and scared. Almost a half of the athletes had a very high motivation for recovery and most of them recovered successfully. Social support mostly came from their families, followed by teammates and friends, and also their coaches. When we compared the differences by gender, we realised that male athletes are more likely to get injured than female athletes, who are more likely to be more concerned about the injury.
Keywords: motivacija; rehabilitacija; socialna opora; šport; športne poškodbe; športniki